Political Violence and Democracy in Western Europe, 1918-1940
XI, 208 p.
Keywords: The essays in this book concern manifestations of political violence in the democracies of interwar Europe. While research in this area usually focuses on the countries that fell to fascism, the authors demonstrate that violence remained a part of political competition in the democratic regimes of Western Europe too.